Interdisciplinary relations between historical content and the reading component in primary school - Portela Bravo, Eilene; Martínez Rivera, Taimy; Díaz Suárez, Santiago (Revista Minerva, 2022)
The work goes to solve the problem related with the weak preparation of the educational ones of fifth grade of the Diluted municipality of Passengers to integrate the contents of History of Cuba in the component reading. For it was elaborated it a proposal of activities varied in correspondence with readings of the book of the grade, of educational software and of other texts. Methods were used like: analytic synthetic, inductive deductive, the observation, analysis of documents, interviews and percentage analysis. With the application of the proposal of activities it was achieved the teachers to be prepared to establish the interdisciplinary relationships between the readings and History of Cuba. It was verified that these they were satisfied by the form in that the contents and the activities were conceived, as well as the preparation reached with this proposal.